Metaphor in Students’ English Poems: A Psycholinguistic Analysis - Adriansyah Abu Katili (Jambura Journal of English Teaching and Literature, 2021)
This research is aimed at finding how the students of English Department of State University of Gorontalo perceive the thing as revealed in the metaphor they used in their English Poem and, as well, interpreting the metaphor. This research was designed in qualitative research methodology. The subject of research was the poems written by the students in 2010. It is found that the students used metaphor to express their feeling. The metaphor reflects the students’ perception of the reality categorized in semantic fields. In terms of the intended meaning of the metaphor, the researcher inferred the meaning by finding the metaphor predications based on the researcher knowledge of the predication.